49x-27=2-1.5

Simple and best practice solution for 49x-27=2-1.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49x-27=2-1.5 equation:


Simplifying
49x + -27 = 2 + -1.5

Reorder the terms:
-27 + 49x = 2 + -1.5

Combine like terms: 2 + -1.5 = 0.5
-27 + 49x = 0.5

Solving
-27 + 49x = 0.5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 49x = 0.5 + 27

Combine like terms: -27 + 27 = 0
0 + 49x = 0.5 + 27
49x = 0.5 + 27

Combine like terms: 0.5 + 27 = 27.5
49x = 27.5

Divide each side by '49'.
x = 0.5612244898

Simplifying
x = 0.5612244898

See similar equations:

| -(4m-3)=-3(m-2) | | 28000+3000x=6000x+18000 | | 28000+3000x=8000x+18000 | | 28000+3000x=5000x+18000 | | 28000+3000x=1600x+18000 | | 3+6x-2x=35 | | 28000+3000x=1000x+18000 | | 14x+7y=0 | | 28000+3000x=200x+18000 | | 4(2x-1)=68 | | 28000+3000x=3000x+18000 | | 7x+6(x-4)=x | | 28000+3000x=2500x+18000 | | N-4n+2=20 | | 28000+3000x=2000x+18000 | | 28000+3000x=3500x+18000 | | 4.7x+6(x-4)=x | | 8(t-7)-3(t-4)=6(t-7)+8 | | (7P+1)X^2+(5P-1)X+P=1 | | -6(m-6)=-8(m-1) | | 5-3(x-4)=16 | | f(x+1)=2x^2+3x-4 | | 4(2n-3)=20 | | 25.50+6p=45 | | 25x^2-30x-7=-7 | | 5r=53 | | 2x+105+2x+70+x+8+105=360 | | s+s=10 | | 5-2y=0 | | 2p=8-3(p-4) | | 5(x+4)=4 | | 191=146-y |

Equations solver categories